Enhancing facility layout design using quality function deployment (QFD) approach / Masalina Md Ali - Md Ali, Masalina (2011)
Modern manufacturing facility experiences significant changes in product designs, process plans, demand volumes, product mix, product life cycles and production routings. However, limited attention paid to facilities design layout has resulted in a significant shortcoming especially when a wrong selection of machines/workers position increases the travel distance and thus led to 10 to 30 percent increment in material handling cost. A study on integrating QFD approaches with simulation modelling within a facility layout is thus demonstrated which encompasses: (i) identifying the current practice of facilities layout design through assessment in three different manufacturing environments; (ii) adopting Quality Function Deployment (QFD) method to verify the expectation of the customer/worker requirements for facility layout design characteristics and (iii) analysing the outcomes via simulation modelling to allow verification of the floor design without having to rearrange the actual physical layout. Findings revealed that QFD approach is possible to prioritize and implement the new layout solutions at the onset of the design stage before the actual layout implementation. Six characteristics are concluded as the major primary specification for the facility layout design leaving six others as minor. Besides being relevant for enhancing facility layout problems, it is envisage that findings from this study would further catalyse knowledge and technology advancement indicated in the recommendations.